Towards a Creative Age? - Žažar, Krešimir (Array, 2010)
Here we are discussing an issue of appropriate identity labels for describing modern society. The issue, present since the early days of sociology, is still very current today. Among various terms and theoretical concepts, we find a concept of ‘creative society’ as, potentially, most fruitful one. However, a great caution is required while using this concept since it is conceived more as an analytical tool for examination of direction in which contemporary society is heading for than as an appropriate mark for describing essential character of the society we live in.